Oncoradiology Preparedness in the COVID-19 Pandemic: Perspective from a Tertiary Oncology Referral Center from Eastern India - Chatterjee, Argha; Biswas, Bivas K; Gehani, Anisha; Das, Jayanta; Sen, Saugata; Mukhopadhyay, Sumit; Chandra, Aditi; Ghosh, Priya; Gupta, Bharat; Lingegowda, Dayanand (Indian Journal of Medical and Paediatric Oncology, 2020)
At the time of writing this article, more than 18 million people worldwide have been infected by the severe acute respiratory syndrome-associated coronavirus-2 and about 700,000 people have died from coronavirus disease 2019 (COVID-19). In India, about 190,000 people have been infected and nearly 39,000 people have succumbed to this infection. Infection among health-care workers has emerged as one of the key problems in facing this pandemic. The purpose of this article is to describe the measures taken by the department of oncoradiology at our institution to control the infection and minimize staff exposure during the current lockdown period with reduced patient load and in the post-lockdown period with increased demand for radiology services. The key focus of this article is the continued delivery of cancer imaging services with practical precautions and optimized resources. We have also discussed algorithms and protocols unique to the practice of oncoradiology in the time of the COVID-19 pandemic.
Keywords: Coronavirus disease 2019; oncoradiology; personal protection; preparedness